Legality of Copyright Protection on Artificial Intelligence Works - I Ketut Gede Adi Ramadika; I Ketut Kasta Arya Wijaya (Pemuliaan Keadilan, 2025)
The advancement of artificial intelligence (AI) technology has brought significant challenges to the legal system, especially regarding copyright protection. The ability of AI to produce works independently raises questions about originality, ownership, and legal responsibility. Existing legal systems are designed to protect human works, so they are not fully prepared to accommodate AI innovation. This article discusses the legal challenges presented by AI works and how the law can adapt to provide adequate protection. Approaches such as expanding the definition of originality, regulating contribution-based ownership, and harmonizing international policies are proposed as solutions. With inclusive regulation and responsive law enforcement, it is hoped that the legal system can maintain a balance between encouraging technological innovation and protecting human creative rights.